Tinjauan Fiqh terhadap Wakaf Produktif Menuju Kesejahteran Umat - Pulungan, Sahmiar (DIKTUM: Jurnal Syariah dan Hukum, 2022)
In Indonesia, waqf does plays a role and function in tide of worship. Waqf is expected to help the people economy. The purpose of this study is to explain the productive waqf of Ustman Bin Affan model as a reference in the current implementation of productive waqf. This research is a qualitative descriptive research with a library research approach which is studied using a philosophical approach. This study uses primary data sources, namely data which is the main source of literature research by searching various literatures (books) and as secondary data are journals related to this research. Data collection techniques use the documentation method, namely studying and searching for data in the form of notes, documents, transcripts, books, magazines, and so on. Data analysis is carried out by giving meaning and studied by comparing it with previous research on phenomena that occur in society. The result of the study is hoped tobe a pilot project for the development of productive waqf in Indonesia.